At-Sea Distribution and Prey Selection of Antarctic Petrels and Commercial Krill Fisheries - Descamps, Sébastien; Tarroux, Arnaud; Cherel, Yves; Delord, Karine; Godø, Olaf Rune; Kato, Akiko; Krafft, Bjørn A.; Lorentsen, Svein-Håkon; Ropert-Coudert, Yan; Skaret, Georg; Varpe, Øystein (PloS one, 2016)
Commercial fisheries may impact marine ecosystems and affect populations of predators like seabirds. In the Southern Ocean, there is an extensive fishery for Antarctic krill Euphausia superba that is projected to increase further. Comparing distribution and prey selection of fishing operations versus predators is needed to predict fishery-related impacts on krill-dependent predators. In this context, it is important to consider not only predators breeding near the fishing grounds but also the ones breeding far away and that disperse during the non-breeding season where they may interact with fisheries. In this study, we first quantified the overlap between the distribution of the Antarctic krill fisheries and the distribution of a krill dependent seabird, the Antarctic petrel Thalassoica antarctica, during both the breeding and non-breeding season. We tracked birds from the world biggest Antarctic petrel colony (Svarthamaren, Dronning Maud Land), located >1000 km from the main fishing areas, during three consecutive seasons. The overall spatial overlap between krill fisheries and Antarctic petrels was limited but varied greatly among and within years, and was high in some periods during the non-breeding season. In a second step, we described the length frequency distribution of Antarctic krill consumed by Antarctic petrels, and compared this with results from fisheries, as well as from diet studies in other krill predators. Krill taken by Antarctic petrels did not differ in size from that taken by trawls or from krill taken by most Antarctic krill predators. Selectivity for specific Antarctic krill stages seems generally low in Antarctic predators. Overall, our results show that competition between Antarctic petrels and krill fisheries is currently likely negligible. However, if krill fisheries are to increase in the future, competition with the Antarctic petrel may occur, even with birds breeding thousands of kilometers away.